2012
DOI: 10.26719/2012.18.5.480
|View full text |Cite
|
Sign up to set email alerts
|

480 Relationship between consultation length and rational prescribing of drugs in Gorgan city, Islamic Republic of Iran

Abstract: Doctors with longer consultation times tend to diagnose illnesses more precisely, prescribe fewer drugs and present better health advice to their patients. The aim of this study was to measure the average consultation time of general practitioners in Gorgan, Islamic Republic of Iran and to investigate the factors affecting consultation length, especially in relation to rational prescribing of drugs. Data were collected on 620 patient consultations with 62 randomly selected general practitioners. Mean consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…GPs as percentage of medical workforce in the primary health-care services were very low in Iran (24.1%)[35] as compared to wealthier countries like Australia (43%)[27] and the UK (40%). [2128]…”
Section: Discussionmentioning
confidence: 99%
“…GPs as percentage of medical workforce in the primary health-care services were very low in Iran (24.1%)[35] as compared to wealthier countries like Australia (43%)[27] and the UK (40%). [2128]…”
Section: Discussionmentioning
confidence: 99%
“…In Gorgan City, Islamic of Iran, doctors with longer consultation time more precisely, prescribe fewer drugs and present better health advice to the patients. The total mean consultation was 6.9 minutes, and mean consultations time for GP's in the city were shorter than those in village (6.7 versus 7.5) minutes [5]. The 2nd ICHA A research by Cape found that the mean durations of the consultations was 9.9 minutes; 60% patients over-estimated the length of their consultations and 40% patients under-estimated the length of consultations.…”
Section: Discussionmentioning
confidence: 94%
“…As for Tunisia, the local researcher facilitated the meeting, with clear detailed guidance provided by the core research team prior to the meeting. The priority setting meetings served the following two purposes1: validate the list of research questions related to quality, safety and performance management in PHC (generated from the gap map); and2 subsequently rank the validated questions against a set of specific criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The Alma-Ata Declaration envisioned primary health care (PHC) as an integral part of a country’s health system and of the overall social and economic development of the community 1. Strong and comprehensive PHC leads to better health outcomes, improves health equity, reduces inefficiencies of health systems and accelerates achievement of the health-related sustainable development goals (SDGs) including the transformative aim of universal health coverage (UHC) 2–5.…”
Section: Introductionmentioning
confidence: 99%